Prediction of pneumonia in a pediatric emergency department - Neuman, Mark I; Monuteaux, Michael C; Scully, Kevin J; Bachur, Richard G (Pediatrics (Evanston), 2011)
To study the association between historical and physical examination findings and radiographic pneumonia in children who present with suspicion for pneumonia in the emergency department, and to develop a clinical decision rule for the use of chest radiography. We conducted a prospective cohort study in an urban pediatric emergency department of patients younger than 21 who had a chest radiograph performed for suspicion of pneumonia (n = 2574). Pneumonia was categorized into 2 groups on the basis of an attending radiologist interpretation of the chest radiograph: radiographic pneumonia (includes definite and equivocal cases of pneumonia) and definite pneumonia. We estimated a multivariate logistic regression model with pneumonia status as the dependent variable and the historical and physical examination findings as the independent variables. We also performed a recursive partitioning analysis. Sixteen percent of patients had radiographic pneumonia. History of chest pain, focal rales, duration of fever, and oximetry levels at triage were significant predictors of pneumonia. The presence of tachypnea, retractions, and grunting were not associated with pneumonia. Hypoxia (oxygen saturation ≤92%) was the strongest predictor of pneumonia (odds ratio: 3.6 [95% confidence interval (CI): 2.0-6.8]). Recursive partitioning analysis revealed that among subjects with O₂ saturation >92%, no history of fever, no focal decreased breath sounds, and no focal rales, the rate of radiographic pneumonia was 7.6% (95% CI: 5.3-10.0) and definite pneumonia was 2.9% (95% CI: 1.4-4.4). Historical and physical examination findings can be used to risk stratify children for risk of radiographic pneumonia.